1986
DOI: 10.2105/ajph.76.12.1432
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a risk factor for infertility with ovulatory dysfunction.

Abstract: To examine the relation of regular vigorous exercise to ovulatory infertility, we interviewed 346 infertile women, in whom there was evidence of ovulatory failure, regarding their exercise patterns during the year preceding their unsuccessful effort to conceive. Their responses were compared with similar exercise histories in women who had successfully conceived at the time the infertile women started trying to become pregnant. Vigorous exercise for an hour or more per day was reported more commonly in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Biologic evidence supports a hypothesis that physical activity affects implantation, and several epidemiologic studies indicate an association between self-reported frequent vigorous activity and fertility (1012). A study of 2,232 infertile women undergoing IVF found that those who reported exercising ≥4 hours/week for the past 1–9 years were less likely to conceive and have a live birth than women without a history of exercising (13).…”
mentioning
confidence: 72%
“…Biologic evidence supports a hypothesis that physical activity affects implantation, and several epidemiologic studies indicate an association between self-reported frequent vigorous activity and fertility (1012). A study of 2,232 infertile women undergoing IVF found that those who reported exercising ≥4 hours/week for the past 1–9 years were less likely to conceive and have a live birth than women without a history of exercising (13).…”
mentioning
confidence: 72%
“…Indices of ovarian suppression, e.g. amenorrhoea, anovulatory cycles and inadequate luteal phases, are associated with dieting and exercise in women from developed countries, and with low-calorie diet and intense workload in women from developing countries (Warren 1983;Prior 1985;Green et al 1986;Howlett 1987;Henley & Vaitukaitis 1988;Ellison et al 1989;Cumming 1993;Rosetta 1993;Panter-Brick & Ellison 1994). However, interpreting the functional signi¢cance of ovarian suppression induced by physical activity has been di¤cult for two principal reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies show that physical stress may influence hypothalamic as well as pituitary function and reproductive performance. [3][4][5][6][7] However, it is questionable to generalise results from extremely fit women with low body fat to women who are exposed to typical, strenuous, occupational exertion. Additionally, most studies on women exposed to strenuous work such as shiftwork, heavy lifting, standing, and psychological job stress, have focused on adverse pregnancy outcomes.…”
mentioning
confidence: 99%